BMC proceedings (BioMed Central, 2007)
BMC Proceedings is a peer-reviewed open access online journal publishing proceedings from conferences, including both peer-reviewed full articles and collections of meeting abstracts. Devoted specifically to conference publications, BMC Proceedings aims to provide open access journal publication for all types of proceedings, including large collections of articles, meetings of specialised interest and conferences of a cross- or multi-disciplinary nature. Content is not restricted to any particular discipline within biomedicine and all proceedings are published without barriers to access.